E-beam evaporated hydrophobic metal oxide thin films as carrier transport materials for large scale perovskite solar cells. (21st March 2022) - Hossain, M. I.; Zakaria, Y.; Zikri, A.; Samara, A.; Aissa, B.; El-Mellouhi, F.; Hasan, N. S.; Belaidi, A.; Mahmood, A.; Mansour, Said
ABSTRACT: E-beam evaporated metal-oxide thin films have been studied with different stoichiometries as carrier transport materials for large-scale perovskite solar cell devices. The thin films are deposited through a reactive evaporation of pure metals in various oxygen atmosphere pressures. The measured optical and electrical properties were used in numerical modelling using SCAPS-1D software to demonstrate a power conversion efficiency in excess of 26%. X-ray photoelectron spectroscopy and optical characterization confirmed the variation of the oxygen concentration into these films with respect to the deposition pressures. The electrical measurements using hall probes complies with the reasonable data range. The field emission scanning electron microscopy demonstrated the deposition of dense, homogeneous and pin-hole-free uniform films throughout the substrate's surface. Hydrophobic surface was found for the films grown with nano-porous structure. In particular, large-scale vapour deposition of perovskite solar cells becomes feasible due to such fabrication technique without breaking the vacuum.